Audit dan Manajemen Energi pada Hotel Quest - Stevanus Widjaja; Togar Panjaitan (Jurnal Titra, 2015)
Quest Hotel previously has not been taking any measurements of energy use that they use for this both in terms of management and technology side. Therefore, this new hotel is relatively have new target for measuring their energy use. After measuring the energy use, it is detected that the use of energy in the Hotel Quest indicate a waste of energy. The benchmark standard of the measurement calculation is IKE or Intensity of Energy Consumption. The proposal will be concentrated in energy saving in the form of replacement lamps, replacement refrigerator until replacement actuator is an effort made to save energy.